Industrial production in Western Europe and the United States 1901 to 1955 - PARETTI, V.; BLOCH, G. (PSL Quarterly Review, 2014)
The article provides a comparative study of the volume, structure and development of industrial production in Western Europe and the Unite States. After a brief description of the methods employed, the study describes the distribution of industrial production in 1955 between the individual countries of Western Europe. The authors then examine the development of industrial production between 1901 and 1955 in Western Europe as a whole, in each of the various Western European countries and in the United States. In comparing the rate of development in the United States with that in Europe, they show that the “falling-behind” of Europe was principally due to the impact of the two world wars. While the structure of industrial production differs from country to country, the structural changes between 1901 and 1955 followed the same course everywhere: the metal products and chemical sectors increased at the expense of the food and textile industries, while the relative share of the basic metal industries remained almost unchanged. The study concludes with an examination of the volume and development of industrial product per head over the same period. JEL: E23, N10